Nuzul Qur'an dan Literasi Digital: Membangun Kesadaran Kritis terhadap Hoaks dan Disinformasi - Nofa Aullia Dzikri Gunawan; Muh. Habibulloh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rapid development of digital media has created a communication pattern in which information spreads quickly and often without verification. In this situation, hoaxes and disinformation have emerged as a serious threat that affects social trust, religious harmony, and individual behavior in online spaces. This study aims to explore Qur’anic principles that are relevant for building critical awareness, especially through the momentum of Nuzul Qur’an as an illustration of revelation that guides people in understanding messages accurately. The research uses a qualitative descriptive-analytical design with a thematic tafsir approach to examine verses related to verification, prohibition of false speech, and speaking truth. Primary sources consist of the Qur’an and classical as well as modern commentaries, while secondary sources include books and scientific articles on digital literacy and misinformation. The findings show that Qur’anic principles such as tabayyun, avoidance of false accusation, and responsibility in communication are aligned with core elements of digital literacy that require users to identify reliable sources and evaluate messages before sharing. The conclusion suggests that integrating Qur’anic ethical values into digital literacy programs can reduce the circulation of hoaxes and strengthen a culture of truth in digital interaction.